2014
DOI: 10.7158/s13-006.2014.15.3
|View full text |Cite
|
Sign up to set email alerts
|

Simple hand calculation method for estimating deflection generated by the low velocity impact of a solid object

Abstract: Codifi ed provisions for estimating impact actions in contemporary codes of practices are convenient to apply but lack generality given that parameters associated with the inertia resistance of the target have not been incorporated into the provisions. This paper introduces algebraic expressions for estimating the maximum defl ection of a structural member when subject to the hard impact action of a fl ying, or fallen, impactor (or projectile). Once the defl ection value is known the equivalent static force va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This may represent quite well the impact of a pressurised sport ball on a hard ground such concrete or wooden floor that may be encountered in basketball or handball. Differently, for outdoor sports such as football or rugby, the field is soft enough to be deformed elastically or plastically by the ball during the impact, changing the properties of impact [28,29]. This remark stands also for impact of pressurized balls or pressurised protections on humans which soft tissues (skin, muscles, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This may represent quite well the impact of a pressurised sport ball on a hard ground such concrete or wooden floor that may be encountered in basketball or handball. Differently, for outdoor sports such as football or rugby, the field is soft enough to be deformed elastically or plastically by the ball during the impact, changing the properties of impact [28,29]. This remark stands also for impact of pressurized balls or pressurised protections on humans which soft tissues (skin, muscles, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The model was derived by the authors based on fundamental principles of energy and momentum. Analytical expressions for predicting the displacement demand of the impact have until now only been verified by impact on miniature models made of steel or wooden materials (refer Ali et al (2014), Lam and Gad (2016), Lam et al (2018b), Yang et al (2012)). For the design of a RC barrier walls, which are expected to respond within the elastic limit, the model takes the form of Equation (2).…”
Section: Displacement-based Analytical Modelmentioning
confidence: 99%
“…Parameter defines the ratio of the generalised mass of the target ( ) to the mass of the impactor ( ). The value of may be taken as a quarter of the mass of the stem wall based on established structural dynamics principles (Ali et al 2014, Sun et al 2016. This was derived based on the shape profile of a cantilevered wall, and will remain unaffected by crack formation as long as the limit of yield has not been surpassed.…”
Section: Displacement-based Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that, although the contact force may cause localised damage, only a small fraction of the force is actually transmitted to the rest of the structure due to its inertial resistance (Ali et al 2014;Sun et al 2014). Therefore, the contact force generated by an impact could be an order of magnitude higher than the reaction force that the foundation need be designed to resist.…”
Section: Introductionmentioning
confidence: 99%